Dampak Penurunan IHSG terhadap Stabilitas Ekonomi Publik Indonesia: Analisis Penyebab, Implikasi, dan Strategi Kebijakan - Hafifa, Nur; Maisaroh, Siti; Umaira, Putri Nabilah; Pangestoeti, Wahjoe (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The significant decline of the Indonesia Stock Exchange Composite Index (IHSG) in mid-2025 has become a major focal point in the dynamics of Indonesia’s economy. As a reflection of investor confidence in the national economic conditions, the IHSG showed a downturn triggered by a combination of external factors such as global geopolitical tensions, falling commodity prices, and the U.S. Federal Reserve’s interest rate policy as well as domestic factors including capital outflows and a weak fiscal response. This study aims to analyze the IHSG plunge from a public economics perspective, particularly highlighting the role of the state through fiscal and monetary policies, as well as institutional interventions by authorities such as the Financial Services Authority (OJK) and Bank Indonesia (BI) in maintaining economic stability. The analysis reveals that delayed policy responses and insufficient protection for domestic investors are critical contributing factors. Collaborative measures across institutions are required to restore market confidence and prevent long-term damage to the national economy.